(untitled) (Journal of Geography and Environmental Management, 2018)
Comprehensive analysis of fund resources of the Department of Tourism and Markakol and West-Altai state nature reserves has been completed. Main problems of the tourism industry have been identified. Quantitative and qualitative values of recreational potential have been determined for the main areas of the analyzed territory in different nature complexes to correct and address the problems. Field study results have confirmed that recreational opportunities of nature and tourist destinations of East Kazakhstan region are viable. Health tourism cluster development model has been developed for the region based on the modeling and excursion techniques. Science Department of Markakol and West Altai state nature reserves has suggested an eco path guided tours.